1854 Miss. Laws 49–50, ch. 1, § 1 - (:unkn) unknown (General Publisher, 1854)
Imposed an annual property tax of $1 on each Bowie knife, Arkansas toothpick, sword cane, and dueling or pocket pistol.
--
Keywords: TAX - PROPERTY OR SALES